Pengaruh Penggunaan Lectora Inspire Terhadap Kemampuan Berpikir Kritis Siswa SMAN 49 Jakarta Pada Mata Pelajaran Geografi - Rifni Aulia Safitri; Ahman Sya; Ilham Badaruddin Mataburu (LPPM Politeknik Pratama, 2023)
This study aims to determine the effect of using Lectora Inspire learning media on the critical thinking skills of class XI IPS students at SMAN 49 Jakarta in the subject matter of geography on Indonesian cultural diversity. Using a quasi-experimental method with a sampling technique that is total sampling. The sample used was class XI IPS 2 as an experimental class that used Lectora Inspire learning media and class XI IPS 1 as a control class that used PowerPoint learning media. The research instrument test was declared valid and reliable, and the data obtained was normal and homogeneous. The results of the statistical test (independent sample t test) obtained the value of sig. of 0.014 which means H0 is rejected and Ha is accepted due to the Sig value. < 0.05. The conclusion of the study is that there is an effect of using Lectora Inspire learning media on students' critical thinking skills in the experimental class. The increase in students' critical thinking skills in the experimental class was higher, namely 3.85, while in the control class it was 2.25.